Monetary Rewards, Hierarchy Level and Working Hours as Drivers of Employees' Self-Evaluations - Christian Grund; Alexandra Soboll (Institute of Labor Economics (IZA), 2023)
In this study, we explore the relation between job characteristics and employees' self-evaluations of performance in comparison to their colleagues' performance. Making use of unique individual panel data of ten large firms in Germany's chemical industry, we focus on monetary rewards (bonus payments and wage increases), level of hierarchy and weekly working hours as well as interactions with gender and tenure as possible drivers of self-evaluations. Our results hint for particular relevance of working hours, and some extent of hierarchy levels and monetary rewards. We find less evidence for our hypotheses regarding interaction effects of gender and tenure.
Keywords: J3; M5; 330; self-evaluations; bonus payments; wage increases; level of hierarchy; working hours